КРИТЕРИИ ОЦЕНКИ ЭФФЕКТИВНОСТИ ОСУЩЕСТВЛЕНИЯ КОНТРОЛЯ ЗА КАЧЕСТВОМ ВЫСШЕГО ОБРАЗОВАНИЯ - Невядовський, Владислав Олегович (SUPREMANCE OF LAW, 2017)
The article, based on the analysis of the scientific views of scientists and the norms of the current legislation, defines the criteria for assessing the effectiveness of monitoring the quality of higher education in Ukraine. It is noted that the range of criteria by which the effectiveness of control over the quality of higher education should be assessed is not static, but their list should be flexible and relevant in order to always provide the most objective data on the state of the effectiveness of this control.